Gambaran Pengetahuan Wanita Usia Subur dalam Melakukan Pemeriksaan Pap Smear Dengan Menggunakan IVA Test di Wilayah Kerja Puskesmas Kota Tengah - Muhamad, Zuriati; Harismayanti, Harismayanti; Nunu, Fitriyyah R. (Universitas Malahayati, 2025)
ABSTRACT The majority of women worldwide are afflicted with cervical cancer, a disease that impacts their reproductive health. The significance of cervical cancer preventive programs using Pap smears is demonstrated by the high freguency of cervical cancer cases in Indonesia. The purpose of this study is to use the IVA test in Central City health centers to describe the knowledge of women of reproductive age regarding Pap smear tests. The knowledge of women of reproductive age on doing Pap smear examinations with the IVA test is described by this study technigue utilizing a descriptive approach. This research method uses a descriptive approach to describe the knowledge of women of childbearing age in carrying out Pap smear examinations using the IVA test. Sampling was taken using Stratified random sampling technique with a sample size of 91. The results of this research showed that 65.6% of respondents had good knowledge regarding the knowledge of women of childbearing age in carrying out pap smear examinations, and 17.8% of respondents had sufficient knowledge, while 16.7% of respondents had insufficient knowledge. Then we got a picture of the knowledge of women of childbearing age in using the IVA test, that there were 57.8% of respondents who had good knowledge, and 21.1% of respondents who had sufficient knowledge, while those who had less knowledge were 21.1% of respondents.Conclusion : The majority of women at the Central City Health Center who.are of childbearing age have strong knowledge, according to the esearchers findings, and having more schooling does not always eguate to having good-knowledge. This study demonstrated that knowledgeable persons are more /ikely to e found at lower educational levels than at higher ones. Keywords: Pap Smear, Women of Childbearing Age: IVA Test, Cervical Cancer ABSTRAK Kanker serviks merupakan penyakit yang mempengaruhi kesehatan reproduksi wanita dan merupakan jenis kanker yang paling banyak diderita wanita di seluruh dunia Tingginya angka kejadian penderita kanker serviks di Indonesia, menunjukkan pentingnya program pencegahan kanker serviks dengan pap smear. penelitian ini untuk mengetahui Gambaran Pengetahuan Wanita Usia Subur dalam Pemeriksaan Pap Smear Menggunakan IVA Tes di puskesmas Kota Tengah. ini menggunakan pendekatan deskriptif untuk menggambarkan Pengetahuan Wanita Usia Subur dalam Melakukan Pemeriksaan Pap Smear menggunakan IVA Test. Pengambilan sampel dengan tehnik Stratified random sampling dengan jumlah sampel 91. ini Didapatkan gambaran tentang pengetahuan Wanita Usia Subur dalam melakukan pemeriksaan pap smear sebanyak 65.6% responden berpengetahuan baik, dan 17.8% responden yang memiliki pengetahuan cukup, sedangkan yang memiliki pengetahuan kurang sebanyak 16.7% responden. Kemudian Didapatkan gambaran tentang pengetahuan Wanita Usia Subur dalam menggunakan IVA test bahwa terdapat 57.8% responden berpengetahuan baik, dan 21.1% responden yang memiliki pengetahuan cukup, sedangkan yang memiliki pengetahuan kurang sebanyak 21.1% responden. Temuan peneliti menghasilkan kesimpulan bahwa sebagian besar Wanita Usia Subur di Puskesmas Kota Tengah memiliki Pengetahuan Baik, serta pendidikan tinggi belum tentu memiliki pengetahuan yang baik. Dibuktikan dalam penelitian ini bahwa yang memiliki pengetahuan baik lebih banyak terdapat pada tingkat pendidikan rendah dibanding tingkat pendidikan tinggi. Kata Kunci: IVA Test, Kanker Serviks, Pap Smear, Wanita Usia Subur